Characterization of an ²⁴¹Am-Be neutron irradiation facility at Institute for Nuclear Science and Technology - Tran, Ngoc Toan; Chu, Vu Long; Bui, Duc Ky; Nguyen, Duc Kien; Nguyen, Duc Tam (Nuclear Science and Technology, 2017)
An automated panoramic irradiator with a 241Am-Be neutron source of 5 Ci is installed in a bunker-type medium room at the Institute for Nuclear Science and Technology (INST) for calibration of neutron devices. Bonner Sphere Spectrometer (BSS) formed by 6 spheres plus bare detector, with cylindrical, almost point like, 6LiI(Eu) scintillator and 2 different spectral unfolding FRUIT and BUNKIUT codes are used to characterize the neutron field in different measurement points along the irradiation bench. The neutron field is also simulated by MCNP5 software and compared with measurements performed by the BSS. The paper shows the main results obtained in terms of neutron spectra at fixed distances from the source as well as their neutron fluence rate (total and direct) and ambient dose equivalent rate. These values measured by the BSS with two unfolding FRUIT and BUNKIUT codes are in good agreement with that of simulated by MCNP5 within 10%.